Synthesis of Cu-Ag core-shell nanoparticles and its electrochemical characterization - Laurencia G. Sutanto; Yeremia B. Cristian; Jihan N Adzijah; Imanda Widianti; Prastika Krisma Jiwanti (Journal of Advanced Technology and Multidiscipline, 2023)
The Cu-Ag core-shell nanoparticles (Cu@Ag NPs) are prepared by chemical reduction method with polyvinyl pyrrolidone (PVP) was used as a capping agent, ascorbic acid (C6H8O6) and sodium borohydride (NaBH4) was used as a reducing agent. Cu@Ag NPs were synthesized with three variations of (Cu:Ag) 1:3, 1:4, and 1:5.. The uniformity of Cu@Ag NPs samples with three variations was verified by the particle size analyzer test. The sizes of Cu@Ag 1:3, 1:4, and 1:5 was obtained sequentially at the range of 270-280 nm, 300-304 nm, and 690-700 nm respectively. Indications of the successful synthesis of Cu@Ag nanoparticles can be seen from UV-Vis spectra of Cu@Ag 1:3, 1:4, and 1:5 respectively forming AgNP at wavelengths of 434 nm, 450 nm, and 428 nm Furthermore, the stability of Cu@Ag NPs was carried out over a period of 0 days, 4 days, 7 days, 11 days, and 14 days. It can be observed that the variation of 1:5 tends to be more stable as the chart continues to experience significant improvements compared to the variation of 1:3 and 1:4. The electrochemical study was then performed by applying cyclic voltammetry from 0 V to 1.8 V. It is clearly shown that the peak of Cu oxidation is appeared at a potential of 1.2 V while the peak value of Ag oxidation is at a potential of 0.9 V.